Explaining the presence of perennial liquid water bodies in the firn of the Greenland Ice Sheet. Issue 2 (21st January 2014) - Munneke, P. Kuipers; M. Ligtenberg, S. R.; van den, M. R.; van, J. H.; Forster, R. R.
<x xml:space="preserve">Abstract</x> Recent observations have shown that the firn layer on the Greenland Ice Sheet features subsurface bodies of liquid water at the end of the winter season. Using a model with basic firn hydrology, thermodynamics, and compaction in one dimension, we find that a combination of moderate to strong surface melt and a high annual accumulation rate is required to form such a perennial firn aquifer. The high accumulation rate ensures that there is pore space available to store water at a depth where it is protected from the winter cold. Low‐accumulation sites cannot provide sufficiently deep pore space to store liquid water. However, for even higher accumulation rates, the total cold content of the winter accumulation becomes sufficient to refreeze the total amount of liquid water. As a consequence, wintertime or springtime observations of subsurface liquid water in these specific accumulation conditions cannot distinguish between a truly perennial firn aquifer and water layers that will ultimately refreeze completely.